(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the application of intraoperative frozen section (FS) and analyze its association with reinfection in second-stage revision arthroplasty for patients with chronic periprosthetic hip joint infection. Materials and Methods: A prospective case series study was conducted on 39 patients with chronic PJI who underwent two-stage revision arthroplasty at Cho Ray Hospital between January 2021 and November 2025. FS was routinely performed during the second stage using five periprosthetic tissue samples, with a negative threshold defined as <5 polymorphonuclear neutrophils per high-power field (x400). Results: The mean age was 51.2 years, and 69.2% of patients were male. Positive bacterial cultures were identified in 74.36% of cases, with methicillin-resistant Staphylococcus aureus (MRSA) being the most common pathogen (41.03%). Positive FS results were observed in 5/39 cases (12.8%). The mean turnaround time for FS results was 40.72 ± 6.6 minutes. After a mean follow-up of 26.9 months, the success rate reached 94.9%. Positive FS results were significantly associated with postoperative reinfection (p = 0.013). Conclusion: Intraoperative frozen section may immediately provide useful information for assessing persistent infection during second-stage reimplantation. FS should be integrated with clinical findings and serological tests to optimize surgical decision-making.